Digital entrepreneurship and accounting training for students at SMKN 3 Central Bengkulu - Noviantoro, Rinto; Ariska, Yesi Indian; Febliansyah, Muhammad Rahman; Dary, Nadya Putri Wulan; Desita, Ridha Tri; Apriansyah, Mogi (Central Community Development Journal, 2022)
Community empowerment is one of the strategies in efforts to implement community development based on the principle of democracy, in which the community is encouraged to be able to place themselves proportionally and become the main actors in improving their own standard of living by accessing and utilizing available resources on an ongoing basis. Community empowerment through activity programs. Training entrepreneurship and digital accounting for students of smk n3 bengkulu central, but there are several obstacles where students do not know the basis for starting entrepreneurship in the digital globalization era, so with the existence of business marketing opportunities in the digital world era, they are honed in training from an early age in order to understand in this all-sophisticated digital era. This program was carried out at SMK N 3 Bengkulu Tengah by students and teachers at SMK N 3 Bengkulu Tengah through presentation of material accompanied by discussions related to optimizing entrepreneurship and digital accounting. Through optimizing media and digital networks in fostering an entrepreneurial spirit it is also